2013
DOI: 10.1111/j.1479-8301.2012.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Expert‐based drug lists to measure anticholinergic burden: similar names, different results

Abstract: Background: Scoring scales such as the Anticholinergic Drug Scale (ADS), the Anticholinergic Risk Scale (ARS), and the Anticholinergic Cognitive Burden Scale (ACB) provide an estimation of total anticholinergic burden. Not all the lists include the same drugs, and the points given for certain drugs differ among them. Whether these discrepancies present important differences in the estimation of anticholinergic burden for an individual patient is unknown. Therefore, the aim of this study is to assess agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 19 publications
5
62
3
2
Order By: Relevance
“…Additionally, a recent study concluded that there was poor agreement between the Anticholinergic Drug Scale, Anticholinergic Risk Scale, and Anticholinergic Cognitive Burden Scale, and suggested the scales could not be applied to varying study settings unless consistently updated 73. Furthermore, it has been proposed that a definitive international list of anticholinergic medications is important to build credible screening tools and to translate research with these scales to associations with clinical outcomes in older adults 46.…”
Section: Comparison Of Drug Burden Index With Other Evidence-based Phmentioning
confidence: 99%
“…Additionally, a recent study concluded that there was poor agreement between the Anticholinergic Drug Scale, Anticholinergic Risk Scale, and Anticholinergic Cognitive Burden Scale, and suggested the scales could not be applied to varying study settings unless consistently updated 73. Furthermore, it has been proposed that a definitive international list of anticholinergic medications is important to build credible screening tools and to translate research with these scales to associations with clinical outcomes in older adults 46.…”
Section: Comparison Of Drug Burden Index With Other Evidence-based Phmentioning
confidence: 99%
“…However, data are conflicting as other findings showed for example only sedating benzodiazepines to have an influence on cognitive testing in geriatric patients [10]. Some findings suggest that the actual mechanism of hypnotic action of a drug [30] or maybe rather hypnotic action per se, that disturbs the restorative action of sleep, can have a negative impact on cognition [34] These findings together with a limited insight into the manifold possible influences on the actual pathoetiology of delirium are mirrored by existing scales of anticholinergic properties of drugs [3,4,28], which show poor agreement [20]. Where comparisons to these scales are possible the DEL-FINE scale also differs: the rating of sedative-hypnotic agents, in particular the rating of benzodiazepines, can only be summarized as heterogeneous.…”
Section: Discussionmentioning
confidence: 75%
“…Several scales are available in the literature to score the anticholinergic effect of drugs [3,4,28] but they agree only poorly [20]. This is why this working group felt justified to combine and reanalyze these pre-existing scales to create a consensus tool.…”
Section: Introductionmentioning
confidence: 98%
“…Using the opioid conversion chart for equianalgesia from Oxford Desk Reference/Oncology all opioid doses were converted to subcutaneous morphine sulphate so that a consistent scale variable could be created (Laird & Fallon, ). The anticholinergic load scores of medications prescribed five days before death were determined using the anticholinergic drug scale (ADS) as presented by Lertxundi, Domingo‐Echaburu, Hernandez, Peral, and Medrano () and total scores calculated.…”
Section: The Studymentioning
confidence: 99%